2008
DOI: 10.1172/jci36226
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic human cells inhibit migration of granulocytes via release of lactoferrin

Abstract: Apoptosis is a noninflammatory, programmed form of cell death. One mechanism underlying the non-phlogistic nature of the apoptosis program is the swift phagocytosis of the dying cells. How apoptotic cells attract mononuclear phagocytes and not granulocytes, the professional phagocytes that accumulate at sites of inflammation, has not been determined. Here, we show that apoptotic human cell lines of diverse lineages synthesize and secrete lactoferrin, a pleiotropic glycoprotein with known antiinflammatory prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
183
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(196 citation statements)
references
References 74 publications
2
183
2
4
Order By: Relevance
“…6 Apoptotic cells secrete signals, such as lactoferrin, that inhibit the migration of neutrophils but not of monocytes. 7 In contrast, we show that apoptotic cells killed by doxorubicin induce an acute inflammatory response characterized by recruitment of neutrophils but have no significant effect on recruitment of monocytes. Thus, apoptotic cells challenged with doxorubicin behave like necrotic cells in terms of neutrophil recruitment.…”
Section: N=10 N=12 N=9contrasting
confidence: 57%
See 1 more Smart Citation
“…6 Apoptotic cells secrete signals, such as lactoferrin, that inhibit the migration of neutrophils but not of monocytes. 7 In contrast, we show that apoptotic cells killed by doxorubicin induce an acute inflammatory response characterized by recruitment of neutrophils but have no significant effect on recruitment of monocytes. Thus, apoptotic cells challenged with doxorubicin behave like necrotic cells in terms of neutrophil recruitment.…”
Section: N=10 N=12 N=9contrasting
confidence: 57%
“…Recently, it was shown that apoptotic Burkitt lymphoma cells specifically inhibit neutrophil chemotaxis by secreting lactoferrin, a pleiotropic glycoprotein with anti-inflammatory properties, but they do not affect monocyte chemotaxis. 7 The inhibition of neutrophil recruitment by apoptotic cells represents an effective mechanism for limiting tissue injury and inflammation. It is known that the recruited neutrophils and the release of their proteolytic enzymes contribute to many pathological inflammatory conditions, such as ischemic injury of the heart, 8 lung 9 and skeletal muscle, 10 as well as to toxic insults to the liver 11 and lung.…”
mentioning
confidence: 99%
“…1 They also secrete lactoferrin as a means of promoting the migration of mononuclear leukocytes, while inhibiting the migration of polymorphonuclear leukocytes. 2 Recent results suggest that this paracrine response also aims at fostering tissue remodeling and repair. A C-terminal fragment of perlecan (LG3), released as a consequence of cathepsin L translocation from apoptotic endothelial cells (EC), induces Bcl-xl upregulation and resistance to apoptosis in fibroblasts, mesenchymal stem cells and smooth muscle cells, all of which are pivotal to tissue or vascular remodeling and repair.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Recently, we showed that caspase-3 activation in EC favors the release of connective tissue growth factor (CTGF), 8 which induces the differentiation of fibroblasts into myofibroblasts, a mandatory process in all forms of repair. To date, caspase-3 activation has been implicated in the release of most, if not all, mediators secreted by apoptotic cells, 1,2,6,8 suggesting that the paracrine response is embedded within the effector phase of apoptosis.…”
mentioning
confidence: 99%
“…Besides providing attraction signals for mononuclear cells, ACs further contribute to the resolution of inflammation by secreting lactoferrin, which potently inhibits granulocyte migration in vitro and in vivo (Bournazou et al, 2008). Apparently, resolution of inflammation is intrinsically anchored to the apoptotic process, which secures in an elegant way the clearance of ACs by mononuclear phagocytes, and at the same time prevents the attraction of additional inflammatory cells.…”
Section: Phagocyte Attractionmentioning
confidence: 99%